Comparison of Phytochemical Screening of Ethanol Extracts from The Skin, Seeds, and Fruit of Aceh Rambai (Baccaurea motleyana Mull.Arg) - Ceriana, Ria; Andayani, Thursina; Yuliana, Cut; Hizqiya Al Zuhra, Cut; Nadia, Ayu; Siti Baitul Mikraj; Susila Indrayani, Pocut; Arafah, Siti (The Health Researcher's Journal, 2024)
One of Indonesia's potentially rich plant species is the rambai (Baccaurea motleyana Muell.Arg). The rambai (Baccaurea motleyana Muell.Arg) belongs to a group of fruit-producing plants that grow wildly in Southeast Asian territories, such as Thailand, Malaysia, and Indonesia, particularly in Sumatra and Kalimantan. Closely related to the menteng/kepundung fruit family, the rambai plant is also found in the Aceh region. Known locally as rambe, it grows in the wild and has not been specifically cultivated. The fruit, along with its skin and seeds, has not been utilized specifically by the community for medicinal purposes, making this research significant. Furthermore, there has been no study on the phytochemical screening of various phytochemical contents in the skin and seeds of the rambai fruit. The objective of this study is to qualitatively determine the phytochemical screening results and contents in the ethanol extract of the skin and seeds of the rambai fruit (Baccaurea motleyana Muell. Arg). This research aims to add to the information on the phytochemical richness of the rambai fruit and serve as an initial reference for studies on the extracts of the fruit's skin, seeds, and flesh (Baccaurea motleyana Muell.Arg). The method for preparing the ethanol extract of the skin, seeds, and flesh of the rambai fruit was carried out through maceration using 96% alcohol solvent. The findings of this study indicate that the ethanol extracts of the fruit's skin and seeds contain the same chemical compounds, namely terpenoids, saponins, flavonoids, and phenolics/tannins.